Gas-phase ligation of Cr+/Fe+/Ni+ ions with iodine - Kazazić, Saša (Array, 2009)
Summary:The gas-phase reaction products of Cr+, Fe+ and Ni+ ions produced by laser desorption ionization (LDI) of a stainless steel sample with iodine molecules in a Fourier transform ion cyclotron resonance mass spectrometer (FT ICR MS) uncover differences in the behavior of individual metal ions in the ligation process as well as in the reactions with ubiquitous water: Fe+ being prone to ligation of two (but also to hydrolysis and disappearance), Ni+ to ligation of three and Cr+ preferring to ligate four iodine atoms. The surplus energy of metal ions produced in the excited states enables them to dissociate I2 and exchange charge with the I2 molecules and I atoms forming I2+ and I3+ ions